2014
DOI: 10.1128/iai.02576-14
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Encoded Pgp3 Is a Major Virulence Factor for Chlamydia muridarum To Induce Hydrosalpinx in Mice

Abstract: dHydrosalpinx induction in mice by Chlamydia muridarum infection, a model that has been used to study C. trachomatis pathogenesis in women, is known to depend on the cryptic plasmid that encodes eight genes designated pgp1 to pgp8. To identify the plasmid-encoded pathogenic determinants, we evaluated C. muridarum transformants deficient in the plasmid-borne gene pgp3, -4, or -7 for induction of hydrosalpinx. C. muridarum transformants with an in-frame deletion of either pgp3 or -4 but not -7 failed to induce h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 48 publications
9
137
0
Order By: Relevance
“…Ramsey et al (6) also used the mouse model for defining the role of the plasmid-encoded Pgp3 in the survival of C. trachomatis in the mouse genital tract. This finding was validated in a C. muridarum infection mouse model in which a Pgp3-deficient C. muridarum strain was no longer able to induce hydrosalpinx (18). Pgp3 is an immunodominant antigen that is secreted into the cytosol of the infected cells (19)(20)(21).…”
mentioning
confidence: 79%
“…Ramsey et al (6) also used the mouse model for defining the role of the plasmid-encoded Pgp3 in the survival of C. trachomatis in the mouse genital tract. This finding was validated in a C. muridarum infection mouse model in which a Pgp3-deficient C. muridarum strain was no longer able to induce hydrosalpinx (18). Pgp3 is an immunodominant antigen that is secreted into the cytosol of the infected cells (19)(20)(21).…”
mentioning
confidence: 79%
“…We then further compared the C. muridarum spreading to the GI tract following intravaginal versus intrabursal inoculations. We previously showed that after intrabursal inoculation, there was a delay in live organisms descending to the vagina and being excreted out of the mouse body (8,38). We expected a significant delay of the spreading of the intrabursally inoculated organisms to the GI tract if oral uptake or anorectal contact of the excreted live organisms was required for the chlamydial spreading.…”
Section: Resultsmentioning
confidence: 99%
“…The clone CMUT3G42.2.1 was previously used for transformation with a luciferase expression plasmid designated pGFP-luci-CM (33). For the current study, the CMUT3G5 clone was used for transformation with the same pGFP-luci-CM plasmid (33) as described previously (37,38). Thus, the luciferase-expressing C. muridarum clone used in the current study was designated Nigg3-CMUT3G5-pGFP-Luci or G5-pGFP-Luci for short.…”
Section: Methodsmentioning
confidence: 99%
“…CP009760.1) with that of the reference C. muridarum strain (40), we redesignated this strain Nigg3. To make the luciferase-expressing C. muridarum strain, a recombinant pGFP-luci-CM plasmid or the pGFP:CM plasmid alone (41) was transformed into a Nigg3-derived plasmid-free clone as described previously (13,42). Both the luciferase-expressing C. muridarum strain (designated CMUT3G5-pGFP-Luci [abbreviated CM-luci]) and the C. muridarum strain transformed with green fluorescent protein (GFP) plasmid alone (designated CMUT3G5-pGFP [abbreviated CM-GFP]) were used in the present study, and they were propagated and purified as elementary bodies (EBs) as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…This is because a single inoculation of C. muridarum organisms in the mouse lower genital tract can cause hydrosalpinx and infertility (7)(8)(9), closely mimicking the tubal adhesion, hydrosalpinx, and infertility observed in women urogenitally infected with C. trachomatis (10)(11)(12). Although C. muridarum is not a natural sexually transmitted agent of mice, chlamydiologists have used this model not only to identify both chlamydial (13)(14)(15)(16)(17) and host (1,5,(18)(19)(20)(21)(22)(23)(24) pathogenic determinants but also to define the roles of ascending infection and tubal inflammation in chlamydial induction of hydrosalpinx (9,16,25,26). Nevertheless, questions such as how a self-limited infection with C. muridarum in the mouse genital tract can trigger tubal fibrosis or hydrosalpinx that lasts long after the tubal infection is resolved (9,25) remain unanswered.…”
mentioning
confidence: 99%